SENSITIVITY OF CANDIDA SPP. FUNGI TO NEW DERIVATIVES OF 4H-PYRIDO [4 ´, 3 ´:5,6] PYRANO [2,3-d] PYRIMIDINE - Щербак, О.М.; Андреєва, І.Д.; Казмірчук, В.В.; Волков, Т.О. (World of Medicine and Biology, 2012)
The significant antifungal activity of the derivatives of 4H-pyrido [4´,3´:5,6] pyrano [2,3-d]pyrimidine against museum and clinical strains of Candida spp. fungi by double serial dilutions method was established. The results of studies of the properties of the derivatives of 4H-pyrido [4 ´, 3´:5,6]pyrano[2,3-d]pyrimidine and development of the compounds on their basis for prophylaxis and treatment of diseases of mycotic etiology could be promising.